Structure determination of hydroxytrypargine: A new tetrahydro-beta-carboline toxin from the venom of the spider Parawixia bistriata - Cesar, LMM; Tormena, C. F.; Marques, M. R.; Silva, GVJ; Mendes, M. A.; Rittner, R.; Palma, Mario Sergio [UNESP] (Wiley-Blackwell, 2005)
A new, highly active tetrahydro-p-carboline toxin from the spider Parawixia bistriata, the most-common species of social spider occurring in Brazil, was isolated. The new toxin was identified as 1,2,3,4-tetrahydro-6-hydroxy-beta-carboline (= N-[3-(2,3,4,9-tetrahydro-6-hydroxy-1H-pyrido[3,4-b]indol-1-yl)propyl]guanidine; 3). This type of alkaloid, not common among spider toxins, was found to be the most-potent constituent of the spider's chemical weaponry to kill prey. When P bistriata catch arthropods in their web, they apparently attack their prey in groups of many individuals injecting their venoms. In vivo toxicity assays with 3 demonstrated a potent lethal effect to honeybees, giving rise to clear neurotoxic effects (paralysis) before death. The compound's toxicity (LD50 value) was determined to be ca. 8 ng/g of honeybee. The investigation of the pharmacological properties and neurotoxic actions of 3 may be used in the future for the development of new drugs to be applied for pest control in agriculture.